A89 FUNCTIONAL ANALYSIS OF NEUTROPHIL CYTOSOLIC FACTOR 4 (NCF4) IN THE PATHOGENESIS OF PEDIATRIC INFLAMMATORY BOWEL DISEASE. (1st March 2018) - Batura, V; Moradin, N; Leung, G; Guo, C; Murchie, R; Warner, N; Muise, A
Abstract: Background: Inflammatory bowel disease (IBD) can arise because of various genetic, environmental, immunological and microbial factors, however, the precise pathological mechanisms leading to IBD remains elusive. Recent advances in genomics have identified multiple genes that cause monogenic IBD. Genetic variants in the Nicotinamide Adenine Dinucleotide Phosphate (NADPH) oxidase have been reported to increase susceptibility of Very Early Onset Inflammatory Bowel Disease (VEOIBD). This multi-protein enzyme complex is involved in the production of superoxide anions (O2 - ), causing a respiratory burst that leads to the formation of hydrogen peroxide and hypochlorous acid for bactericidal activity. A notable histopathological feature of a subset of Crohn's Disease (CD) patients is the formation of granulomas in the gastrointestinal (GI) tract. This is also commonly seen in Chronic Granulomatous Disease (CGD). CGD patients are unable to mount a respiratory burst to defend against bacterial infections. Aims: In this study, two sisters are reported with CD who were diagnosed at ages 7 and 14. Whole exome sequencing identified an autosomal recessive nonsense variant in the NCF4 gene, leading to the truncation of the p40 phox protein, a component of the NADPH oxidase. This study investigated whether this truncation leads to impaired phagocyte oxidase activity which may contribute to the onset of pediatric IBD. Methods: Co-immunoprecipitation (Co-IP) and immunofluorescence (IF) were used to study the effect of this mutation on the interaction of p40 phox with other proteins within the cell. Chemiluminescence assays were used to measure stimuli (PMA and zymosan) induced-oxidative burst over time in RAW264.7 macrophages that stably expressed the wild type and truncated forms of p40 phox . Finally, bacterial killing assays were used to test the ability of these macrophages in pathogen clearance. Results: Co-IP showed a loss of interaction between truncated p40 phox and p67 phox, a component of the NADPH oxidase responsible for formation of a fully activated enzyme. Furthermore, this mutation causes its mislocalization to early endosomes, compared to the cytoplasm location of wild type p40 phox . Finally, chemiluminescence assays show impaired oxidative burst in macrophages stably expressing truncated p40 phox . Conclusions: Taken together, these results suggest that impaired oxidative burst, as a result of this mutation, may be the cause of defective pathogen clearance leading to severe bacterial infections, as seen in the patients. Further validation, using bacterial clearing assays and neutrophils as another model, is warranted to confirm these results. Funding Agencies: CIHRThe Leona M. and Harry B. Helmsley Charitable Trust